2014
DOI: 10.4049/jimmunol.1302338
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Limits Autoimmune Neuroinflammation via Glucocorticoid-Induced Leucine Zipper Expression in Dendritic Cells

Abstract: Autoimmune neuroinflammation, including multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis (EAE), a prototype for T cell–mediated autoimmunity, is believed to result from immune tolerance dysfunction leading to demyelination and substantial neurodegeneration. We previously showed that CNS-restricted expression of hepatocyte growth factor (HGF), a potent neuroprotective factor, reduced CNS inflammation and clinical deficits associated with EAE. In this study, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 29 publications
7
60
0
Order By: Relevance
“…Similar results were reported for the emigration of cutaneous DCs (Langerhans cell, LCs) from the skin [63] or attraction of DCs within the thymus [82]. The importance of HGF in influencing murine immune responses was further powered by studies indicating that in addition to control the migratory process of DCs, HGF could impair murine DC activation [65,70] or confer them with suppressive activities such as the capacity to favor regulatory T cells (Tregs) induction [68,69,83]. Notably, increased DC expression of program-death ligand 1 and IL-27, potent signals for DC-mediated induction of Treg cells, were found to be up-regulated by HGF treatment [83].…”
Section: Dendritic Cells (Dcs)supporting
confidence: 74%
See 1 more Smart Citation
“…Similar results were reported for the emigration of cutaneous DCs (Langerhans cell, LCs) from the skin [63] or attraction of DCs within the thymus [82]. The importance of HGF in influencing murine immune responses was further powered by studies indicating that in addition to control the migratory process of DCs, HGF could impair murine DC activation [65,70] or confer them with suppressive activities such as the capacity to favor regulatory T cells (Tregs) induction [68,69,83]. Notably, increased DC expression of program-death ligand 1 and IL-27, potent signals for DC-mediated induction of Treg cells, were found to be up-regulated by HGF treatment [83].…”
Section: Dendritic Cells (Dcs)supporting
confidence: 74%
“…The importance of HGF in influencing murine immune responses was further powered by studies indicating that in addition to control the migratory process of DCs, HGF could impair murine DC activation [65,70] or confer them with suppressive activities such as the capacity to favor regulatory T cells (Tregs) induction [68,69,83]. Notably, increased DC expression of program-death ligand 1 and IL-27, potent signals for DC-mediated induction of Treg cells, were found to be up-regulated by HGF treatment [83]. Likewise, human DCs differentiated in the presence of HGF were shown to adopt a protolerogenic phenotype with increased ability to generate regulatory T cells [60,84], a property that might be exploited therapeutically in T cell-mediated immune disorders.…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…The GC-Induced Leucine Zipper protein (GILZ) is a GC-induced protein initially reported in dexamethasone (Dex)-treated thymocytes (6). We have previously shown ex vivo that the level of GILZ expression in human DCs controls their tolerance-inducing function (7)(8)(9) and extended to other hematopoietic cells these observations (10,11), which were confirmed by others (12)(13)(14)(15). GILZ expression is partly dependent on endogenous steroids in vivo (12), and its expression in DCs is enhanced in vitro by GC, IL-10, TGF-b (7,8), mitomycin C (16), rapamycin (15), vitamin D3 (15), and tumor environment (17 on DCs (8,9).…”
supporting
confidence: 61%
“…GILZ expression is partly dependent on endogenous steroids in vivo (12), and its expression in DCs is enhanced in vitro by GC, IL-10, TGF-b (7,8), mitomycin C (16), rapamycin (15), vitamin D3 (15), and tumor environment (17 on DCs (8,9). Downregulation of GILZ in DCs promotes the activation of effector CD4 + T cells (8,13,14,17). To gain insight into the impact of GILZ on the regulatory functions of DCs in vivo, we generated CD11c-GILZ hi transgenic mice.…”
mentioning
confidence: 99%
“…13,[24][25][26][27] To determine whether GILZ is expressed in B lymphocytes, BM cells from WT mice were analyzed by qPCR for the expression of GILZ at various stages of B-cell development ( Figure 1A). We have found that GILZ is expressed in all B-cell developmental stages at levels comparable with those of CD4 1 CD25 -T cells, with the highest expression levels of GILZ mRNA detected in mature/recirculating IgM 1 IgD 1 B cells ( Figure 1A).…”
Section: Gilz Is Expressed In B Lymphocytesmentioning
confidence: 99%